The Dynamics of Knowledge Sharing, Trust, And Leadership: Mediating Paths to Competitive Advantage in Agricultural Credit Services - Wanto, Hary; Hariputra, Akbar (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
The agricultural credit from banking sector plays a crucial role in bolstering a country's economic security as one of the key financial institutions. In the contemporary financial landscape, banks are increasingly engaged in fierce competition to provide products and services grounded in knowledge, consumer education, and a high level of trust. This strategic shift is anticipated to create a distinctive competitive advantage. Competitive advantage, an integral part of work outcomes, necessitates substantial support from reinforcing the intellectual tradition of knowledge sharing. Additionally, it relies on robust beliefs manifested through member trust and a leadership style characterized by inclusivity, vision, trustworthiness, and exemplary performance demonstrations. This study builds upon previous research findings and seeks to explore whether knowledge sharing acts as a mediator between trust and competitive advantage. Furthermore, it investigates whether knowledge sharing functions as a mediator between leadership and competitive advantage. To achieve these objectives, the study analyzes a sample comprising 30 branch offices and sub-branch offices of banks in Surabaya, Indonesia. Path analysis is employed for the research methodology, utilizing a multiple linear regression equation model. The results indicate that knowledge sharing serves as an intervention rather than a mediator between the trust variable and the competitive advantage variable. In this context, knowledge sharing weakens the relationship between trust and competitive advantage. On the other hand, knowledge sharing acts as a mediator between the leadership variable and the competitive advantage variable, strengthening their relationship.